Qualitative analysis of nonsmooth dynamics : a simple discrete system with unilateral contact and coulomb friction /: a simple discrete system with unilateral contact and coulomb friction. (2016) - Léger, A (Alain), 1943-; Pratt, Elaine
No abstract available